BØRN I VESTINDISKE FAMILIENETVÆRK: Fire livshistorier fra Nevis - Olwig, Karen Fog (Tidsskriftet Antropologi, 1998)
Karen Fog Olwig: Children in West Indian Family Networks: Four Life Stories from Nevis Caribbean people often leave their children behind with relatives when they migrate. It is well known that these children play an important structural role as central linchpins in networks of social and economic exchange which take place between the migrants and their family in the community of origin. There is, however, little knowledge of the ways in which children themselves experience growing up in these global family networks. This article investigates the point of view of the children by examining four life stories related by young people, from the Leeward Island of Nevis, whose migrant parents left them, as small children, in the care of their grandparents. At a more general level, these life stories also shed light on the cultural values associated with ideals of a good family life among people for whom population mobility and socio-economic connectivity, on a global scale, have long constituted a basic framework of existence.